IMPLIKATUR PERCAKAPAN RADIO: STUDI KASUS ACARA HOT REQUEST RADIO GERONIMO YOGYAKARTA - , IRSYADI SHALIMA, Prof. Dr. Soepomo Poedjosoedarmo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The title of this research is Conversational implicature in Radio: Case Study of Hot Request Program in Geronimo Radio Yogyakarta. This study discusses the implicatures that arise in the telephone conversation. Three topics are described in this study, namely the principles of cooperation, adjacency pair, and implicature. Data obtained by means recorded. After being recorded, the data transcribed. Then, the data is classified and analyzed with the theory of pragmatics. After the analyzed, the data presented in formal language. Based on the results of this study, participants obey to the Griceâs cooperation principles. However, participants also violate Griceâs cooperation principles. In addition, telephone conversations consist of several patterns, namely first part-second part, first partinsertion sequence-second part, first part-insertion sequence-second part-follow up, first partsecond part-follow up, and first part-empty. Meanwhile, conversational implicature consisted of general conversational implicature, conversational implicature scale, specific conversational implicature, and conventional conversational implicature. Based on the results of this research note that participants often violate Griceâs cooperation principles. Violated to the cooperation principles through various patterns of adjacency pair. In addition, violations of Griceâs cooperation principles due to the influence of culture.